A Retrospective Assessment of Soft Tissue Interposition during Redo Surgery for Postoperative Hypospadias Repair-Related Complications - Miyake, Yuichiro; Seo, Shogo; Ishii, Junya; Takeda, Masahiro; Yazaki, Yuta; Ochi, Takanori; Minano, Go; Koga, Hiroyuki; Lane, Geoffrey J.; Yamataka, Atsuyuki (European Journal of Pediatric Surgery, 2025)
To evaluate two established soft tissue interposition techniques used during redo surgery for selected posturethroplasty complications of hypospadias surgery.Patients with complications who had interposition of scrotal fat, tunica vaginalis fascia, or external spermatic fascia identified from all hypospadias patients presenting to a single institute treated by a single surgeon between 2003 and 2019 (n = 217) were reviewed retrospectively. Urethrocutaneous fistula repair and minor cosmetic corrections were excluded.Eight cases had 10 complications: residual penile curvature > 30 degrees (n = 5), urethral diverticulum > 15 mm (n = 3), urethral dehiscence (n = 1), and urethral stricture (n = 1). All were Japanese. Hypospadias was perineal/penoscrotal (n = 7) or midshaft (n = 1). Initial procedures performed in infancy were single-stage urethroplasty (n = 4) or multistage urethroplasty (n = 4). Ages at first soft tissue interposition during redo single-stage urethroplasty (n = 1) or multistage urethroplasty (n = 7; two-stage: n = 4, three-stage: n = 3) ranged from 4.2 to 46.5 years old. All had their neourethras covered and four also had their scarred urethral plates reinforced laterally. There have been no complications during a mean of 5.6-year follow-up after the last procedure (range: 3.4–8.3 years) and all expressed satisfaction with cosmetic and functional outcomes including standing urination. Tissues for interposition were harvested easily without injuring surrounding structures such as the vas deferens or testicular vessels, even though previous surgery had caused extensive adhesions and structural disruption.Unlike reinforcement with tunica dartos fascia, soft tissue interposition specifically boosts tissue thickness and perfusion at the operative site during redo surgery for technically challenging posturethroplasty complications.
Keywords: hypospadias; reoperation; soft tissue interposition; posturethroplasty; complications